Analysis of Extrinsic Elements in the Novel Rindu By Tere - Eka Putri Saptari Wulan; Sarma Panggabean; Ernawati Br Surbakti (Universitas Muhammadiyah Enrekang, 2024)
Literature is the result of a writer's disclosure of the problems of human life in all its aspects, which is a combination of imagination, expression and creativity. Literary works are the author's expression of the world through literary works. The aim of this research is to explain the relationship between extrinsic elements in the sociocultural form of culture depicted in the Novel Rindu by Tere Liye. The data is then classified, interpreted, and studied. The research results show that the Novel Rindu Tere Liye shows the relationship between extrinsic elements and sociocultural and cultural elements in society. This is shown by the combination of two languages, namely Indonesian and Dutch, in the interactions of the characters, and by the knowledge that tells the story of the long journey of the Tere Liye pilgrimage in 1938. The community organization depicted is ordinary people, and the equipment system which is described as still using tr. This study provides an overview of how the external elements of the novel interact with sociocultural and cultural aspects of society.